Analyzing the Centralized Heat Provision of Large Localities in Ukraine and Countries of the World - Kyzym Mykola O. (Research Centre of Industrial Problems of Development of NAS of Ukraine, 2021)
The presented research is aimed at defining the features of organizing the centralized heat provision of large localities in Ukraine and countries of the world. Within the terms of the set aim, the article considers the characteristics of the main heat supply organizations of large cities of Ukraine, the major regional and municipal programs that are effective in them, and the characteristic features of heat supply; the main problems of centralized heat supply in these localities. It is noted that Ukraine displays one of the world’s highest saturation of cities with heat networks: the total length of heat pipelines is approximately 47 thousand km in terms of two-pipe calculation. The share of centralized heating in the total structure of heat supply in Ukraine comprises about 42%. The centralized heat supply system is provided for approximately 60% of the total area, hot water supply – more than 40% of the total area of the country’s housing stock. On the basis of consideration of heat supply systems in several large cities of Ukraine, the general features of their district heating systems are identified. The experience of building a heat supply system in separated countries of the world (Russia, China, Denmark, Finland, USA, Canada, etc.) is analyzed. The scale of district heating systems in the researched world countries is considered. Modern trends in the development of district heating systems in Europe are studied and differences between Ukrainian district heating systems, including in terms of powers of local authorities in the field of heat supply, are determined. It is specified that local authorities in Ukraine are practically deprived of powers to regulate the development of CHP plants and capacities operating on renewable energy sources, which in developed countries is a priority for the development of centralized heat supply.